(untitled) (Revista Educação, Artes e Inclusão, 2022)
The following text presents a theoretical discussion of educational hospital care from the perspective of inclusive education, it is a bibliographic study that reviews terms and situates the reader in the field of hospital pedagogy study. Bringing to light relevant concepts that guide teaching practice in this field still under construction and problematizes the lack of definition that permeates the area. In the textual path, we will trace a brief history of this service placing the reader in time and space, we will bring some concepts of hospital pedagogy and special and inclusive education to define this relationship and understand the field of performance of teachers in this area, technically belonging to the departments of education. Special Education, but often invisible and disregarded as a field of action, as an essential service and as a theoretical construct. For the construction and defense of what we present here, we carried out the search for information on two technical sites: Google academic and Scielo, with the keywords: hospital class, special education and inclusion.